THE INFLUENCE OF CORPORATE CULTURE AND TRANSFORMATIONAL LEADERSHIP AGAINST EMPLOYEE PERFORMANCE MEDIATED BY EMPLOYEE ENGAGEMENT AT PT PLN (PERSERO) UP3 KEBON JERUK - Gusti Ray Hardiyanti; M Havidz Aima; M. Ridwansyah (Dinasti International Journal of Education Management And Social Science, 2022)
This study aims to determine and further analyze the influence of corporate culture and transformational leadership on employee performance with employee engagement as an intervening variable at PT PLN (Persero) UP3 Kebon Jeruk. This study uses quantitative analysis with data collection methods through questionnaires. The population and sample in the study were 63 respondents. The data analysis method used SEM-PLS. The results of the study show that corporate culture has a positive and significant effect on employee engagement, corporate culture has a significant positive effect on performance employees. Transformational leadership has a significant positive effect on employee engagement, transformational leadership has a positive and significant effect on employee performance. Employee engagement has a significant positive effect on employee performance. Employee engagement has a positive but not significant impact mediating corporate culture on employee performance, employee engagement has a significant positive impact mediating transformational leadership on employee performance.